Hunting season [videorecording (DVD)] - Hampton, Adam; Gibson, Mel; Hublitz, Sofia; Hennig, Shelley, 1987-; Buckley, A. J. (Aaron John), 1978-; Trevena, Oliver; Stallone, Scarlet Rose, 2002-; Mollà, Jordi (Samuel Goldwyn Films, 2025)
A girl and her father living deep in the woods, rescue a wounded young woman that washes up on the bank of the local river. Their lives are forever changed by the mysterious stranger, and the ruthless drug lord who will stop at nothing to kill her once and for all.